Representasi Feminisme Dalam Film Enola Holmes - Silvia Rahmayanti (Jurnal Ilmu Komunikasi, 2021)
Film is an embodiment of the representation of life in society through symbols, codes, ideology, mythology, and culture. Film is a popular mass media because it can represent people's lives at a certain place and time. In addition to its function as a medium of communication, film is also an entertaining work of art. The representation from reality showing rules, ideology, and culture. Feminism is an issue that is often raised in contemporary films. Feminism is a movement made by women to get rights and equality in society. One of the films that carries the theme of feminism is Enola Holmes 2. This study aims to examine how feminism in the Victorian era was represented in films. This study uses descriptive qualitative research methods with John Fiske's semiotic analysis method. Semiotics is a method that examines a meaning from the signs displayed. The result of this study is that the film Enola Holmes represents feminism in the 18th century with the signs contained in the film.